Determinan Permintaan Daging Sapi di Provinsi Jambi - Miftahul Hasanah; Zamzami; Selamet Rahmadi (PT. Saha Kreasi Indonesia, 2026)
The purpose of this study is to analyze the influence of beef prices, chicken prices, per capita income, and population on the level of beef demand in Jambi Province during the period 2015–2024. Using a quantitative descriptive method using panel data regression analysis through the Eviews 12 application. The results of the analysis of the research data carried out can be concluded that the demand for beef in Jambi Province is significantly influenced by the variables of beef prices, chicken meat prices, per capita income, and population.